AVALIANDO A AVALIAÇÃO:UM OLHAR ACERCA DO ENADE PEDAGOGIA - Castro, Juliana Contti (2020)
This thesis work has the general objective of understanding the meanings built for the Training profile of the pedagogue and the teacher of the initial years of basic education and the teaching concepts and teaching-learning constructed and reiterat